2020
DOI: 10.1111/mmi.14625
|View full text |Cite
|
Sign up to set email alerts
|

Molecular insights into effector binding by DgoR, a GntR/FadR family transcriptional repressor of D‐galactonate metabolism in Escherichia coli

Abstract: The GntR family of transcriptional regulators (TRs), named after the Bacillus subtilis gluconate operon repressor (Haydon and Guest, 1991), represents one of the largest family of TRs with members present in all three domains of life (El-Gebali et al., 2019;Hoskisson and Rigali, 2009). The members of this family are characterized by the presence of an N-terminal winged helix-turn-helix (wHTH) DNA-binding domain (Pfam, PF00392) and a C-terminal effector-binding and oligomerization (E-O) domain (El-Gebali et al.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 74 publications
1
3
0
Order By: Relevance
“…2i and 2j). These data support DmdR being autoregulatory, consistent with other GntR superfamily regulators [51][52][53] , and the DMSP and acrylate responsive transcriptional repressor of dmdA-acuI and dmdR.…”
Section: Dmdr Represses Dmda-acui Transcription In a Dmsp And Acrylat...supporting
confidence: 79%
“…2i and 2j). These data support DmdR being autoregulatory, consistent with other GntR superfamily regulators [51][52][53] , and the DMSP and acrylate responsive transcriptional repressor of dmdA-acuI and dmdR.…”
Section: Dmdr Represses Dmda-acui Transcription In a Dmsp And Acrylat...supporting
confidence: 79%
“…Bioinformatic analysis showed that PA1520 was found to be another homologue of the FadR subfamily (Fig. S1) (Cronan Jr. and Subrahmanyam, 1998; Gao et al ., 2008; Arya et al ., 2020; Vigouroux et al ., 2021), which led us to investigate the role of PA1520 named UgmR (Uric acid and glyoxylate metabolism regulator) in P . aeruginosa .…”
Section: Resultsmentioning
confidence: 99%
“…The metabolism of D-galactonate, a widely prevalent aldonic sugar acid, is considered to be important for the enteric bacterium E. coli. It metabolizes D-galactonate through the enzymes encoded by D-galactonate operon (dgo) and a modified Entner-Doudoroff pathway (Peekhaus and Conway, 1998), where D-galactonate is degraded into D-glyceraldehyde-3-phosphate and pyruvate, and then enter central metabolism (Singh et al, 2019;Arya et al, 2020). DgoR is encoded by the first gene of dgo operon and negatively regulates the whole operon.…”
Section: Introductionmentioning
confidence: 99%
“…DgoR is encoded by the first gene of dgo operon and negatively regulates the whole operon. DgoR was previously predicted to be a FadR family of transcription regulator, and repress the D-galactonate metabolic pathway by binding inverted repeats in the dgo cis-acting element using D-galactonate as a specific effector molecule (De Ley and Doudoroff, 1957;Deacon and Cooper, 1977;Cooper, 1978;Singh et al, 2019;Arya et al, 2020). Although several regulators of the FadR family have been well described at the molecular level, the binding pocket of Dgalactonate and its substrate specificity have not been investigated (Singh et al, 2019).…”
Section: Introductionmentioning
confidence: 99%